Pharyngeal tongue base augmentation for dysphagia therapy: A prospective case series in patients post head and neck cancer treatment. Issue 8 (4th June 2022) - Schar, Mistyka S.; Omari, Taher I.; Woods, Charmaine M.; Footner, Lauren R.; Marshall, Nicholas; Cock, Charles; Thompson, Alison; Nguyen, Thi; Athanasiadis, Theodore; Ooi, Eng H.
Abstract: Background: Dysphagia post head and neck cancer (HNC) multimodality treatment is attributed to reduced pharyngeal strength. We hypothesized that pharyngeal tongue base augmentation for dysphagia (PAD therapy) would increase pharyngeal pressures during swallowing thereby improving swallow symptoms. Methods: Adults with moderate–severe dysphagia post‐HNC treatment had PAD therapy using a temporary filler (hyaluronic acid [HA]), with follow‐up long‐lasting lipofilling. Swallowing preprocedure and postprocedure was assessed with the Sydney Swallow Questionnaire (SSQ), High‐Resolution Pharyngeal Manometry (HRPM), and Videofluoroscopic Swallowing Study (VFSS). Statistical comparison utilized paired tests. Results: Six participants (all male; median age 64 years [IQR 56, 71]) underwent PAD therapy at a median of 47 [IQR 8, 95] months post‐treatment. SSQ scores reduced from baseline (mean 1069 [95%CI 703, 1434]) to post‐HA (mean 579 [76, 1081], p > 0.05), and post‐lipofilling (491 [95%CI 913, 789], p = 0.003, n = 4). Individual participants demonstrated reduced Swallow Risk Index, Bolus Presence Time, and increased Upper Esophageal Sphincter opening, but mesopharyngeal contractile pressures were unchanged. VFSS measures of aspiration, residue, and severity were unchanged. Conclusions: Novel PAD therapy is safe and improves dysphagia symptoms. Biomechanical swallowing changes are suggestive of more efficacious bolus propulsion with conservative filler volume, but this was unable to resolve residue or aspiration measures.